A Decision Support System for Audit-Staff Scheduling with Precedence Constraints and Due Dates. - Chan, K. Hung; Dodin, Bajis (The Accounting Review, 1986)
ABSTRACT: A versatile computer model for audit-staff scheduling based on a zero-one integer program was presented by Balachandran and Zoltners [1981] (BZ). This paper extends the work of BZ by demonstrating how precedence constraints, due dates, penalty costs, resource leveling, and other audit considerations can be added to the zero-one integer program for audit scheduling. These additional features help improve the realism of the scheduling model, thus making the model more practical for applications.